'I Did Digital Tidying up for a More Adult Stage of Life': Ritualistic Technology Appropriations During Life Transitions. Issue 5 (31st January 2023) - Wolf, Sara; Mörike, Frauke; Löffler, Diana; Hurtienne, Jörn
Abstract: Life transitions, such as the transition from childhood to adulthood, are often accompanied by meaning-making actions such as rituals. Rituals increasingly involve the use of interactive technology. While previous research has focused on specific contexts or technologies, a bird's eye view of the many appropriation styles during life transitions is missing. To identify the range of technology's appropriations, we analysed stories from 84 participants and compared these across different life transitions and technologies. We identified three roles interactive technology can play during life transitions: the role of (i) a facilitator easing the accomplishment of tasks within life transitions, (ii) an enabler creating opportunities for new transition rituals and (iii) a social actor that itself is the trigger or the content of transition rituals. We propose the three roles as a classification scheme to structure existing and future research and reflect on the design challenges and evaluation approaches.